Polish Armenians in Romania (1918–1945) - Pełczyński , Grzegorz (Balcanica Posnaniensia. Acta et studia, 2001)
The article analyzes the history of Polish Armenians living in Romania during the interwar period and the Second World War. The aim of the study is to present the origins of this community, its social position, and its significance for the economic and cultural life of Romania, particularly in Bukovina. The author employs historical and ethnological methods, relying on sources concerning Armenian settlement and the social and political activities of members of this group. The research demonstrates that Polish Armenians originated mainly from former Armenian centers of the Polish-Lithuanian Commonwealth, such as Lwów (Lviv) and Kamieniec Podolski (Kamianets-Podilskyi), and from the late eighteenth century onward settled in large numbers in Bukovina. This community played a significant role in the economic development of the region as landowners, entrepreneurs, and social activists. The author emphasizes that despite progressive assimilation, they retained an awareness of their origins and strong ties to Polish culture. Particular attention is devoted to the political and social activities of Armenian families who belonged to the elites of Bukovina and actively supported Polish national life. The analysis leads to the conclusion that Polish Armenians contributed to the development of education, the press, and social organizations. The community constituted an important element of Romania’s multicultural landscape, combining Armenian heritage with Polish national traditions and playing a significant role in the public life of the region.